Pengaruh CR, DER, NPF Terhadap ROA BMT Nurus Sa’adah Di Pekalongan - Soegiarto Soegiarto (Politeknik Ganesha Medan, 2018)
Performance assessment or performance of a company is measured as the basis for decision making. Financial Performance of a company to know well the bad state of a company. This study aims to determine the influence of accounting informaasi (Current Ratio, Debt to Equity Ratio and Non Performing Ratio) to Financial Performance (ROA). This research is taking Quarterly Financial Report data from 2009 until 2016 KJKS BMT Nurus Sa'adah Pekalongan Regency. Technical analysis used in this study is multiple linear regression that aims to obtain a comprehensive picture of the relationship between variables. While classical assumption test used in this research include autocorrelation test, normality test, multicolonierity test and heteroscedasticity test. The result of this research is that the variable of accounting information that is Current Ratio (CR) and Debt to Equity Ratio (DER) have positive and significant influence to Return On Asset (ROA), Non Performing Financing (NPF) has negative and significant influence to Return On Asset ROA)